Uncertainty quantification in electromagnetic observables of nuclei - Acharya, Bijaya; Bacca, Sonia; Bonaiti, Francesca; Li Muli , Simone Salvatore; Sobczyk, Joanna E. (Frontiers in Physics, 2023)
We present strategies to quantify theoretical uncertainties in modern ab-initio calculations of electromagnetic observables in light and medium-mass nuclei. We discuss how uncertainties build up from various sources, such as the approximations introduced by the few- or many-body solver and the truncation of the chiral effective field theory expansion. We review the recent progress encompassing a broad range of electromagnetic observables in stable and unstable nuclei.